Cold period in the Northern Europe in the past (about 8200 years ago): analysis of empirical data and possible causes - I. I. Borzenkova; O. K. Borisova; E. L. Zhiltsova; T. V. Sapelko (Лëд и снег, 2017)
Cold episode in Northern Europe happened about 8200 years ago was known for a relatively long time, mainly due to paleobotanical (palynological) data obtained from analysis of lake and peat sediments. Detailed analysis of ice cores from the Greenland holes GRIP, GISP2, and NGRIP with a time resolution of about 10 years made possible to refine the duration and characteristics of the time structure of this cold period. This cooling lasted for approximately 160 yr. Spore-pollen analysis of lake sediments in Northern Europe (Sweden, Finland, Denmark, Germany, the North and North-West of Russia) and deep-sea cores of the North Atlantic showed that the mean annual air temperature during the maximum stage of the cooling was reduced by 1–2 °C, and in some areas by more than 3 °C. The cold spread from the coast of the North Atlantic into the European continent and manifested itself mostly in Sweden, Finland, the Baltic States, and to a lesser extent in the North-West and West of the Russian Federation. In the central Russia and North of 70°N the cooling was weak or absent. The question about a nature of this cold event and other cold spells in Late Glaciation, known as the cold of the early, middle and late Dryas, is widely discussed in the scientific literature. Most of scientists accept a hypothesis proposed more than 20 years ago, that the reduction of air temperatures in regions immediately adjacent to the North Atlantic was caused by the large volume of melt water discharged into the ocean as a result of disintegration and melting of ice-sheets. Climate models that take into account these effects allow estimating a decrease in the air and sea surface temperature due to freshening (desalination) of the upper ocean layer, and this confirms that the greatest decrease in temperature should be observed in the regions directly adjacent to the ocean. The increase in global temperature over the last 30 years is estimated to be 0.8 ± 0.2 °C, which is already reflected in a noticeable increase in precipitation in high latitudes. In addition, the melting of mountain glaciers and sea ice in the Arctic basin promotes freshening of the upper ocean, and as a result of these processes one can expect a certain decrease in the air temperature in the high latitudes if the present-day climate warming will continue. On the basis of paleoclimatic data, it can be assumed that such a decrease in air temperature can be relatively small and occur only in areas directly adjacent to the North Atlantic.